2022
DOI: 10.7554/elife.72599
|View full text |Cite
|
Sign up to set email alerts
|

Chemoreceptor co-expression in Drosophila melanogaster olfactory neurons

Abstract: Drosophila melanogaster olfactory neurons have long been thought to express only one chemosensory receptor gene family. There are two main olfactory receptor gene families in Drosophila, the odorant receptors (ORs) and the ionotropic receptors (IRs). The dozens of odorant-binding receptors in each family require at least one co-receptor gene in order to function: Orco for ORs, and Ir25a, Ir8a, and Ir76b for IRs. Using a new genetic knock-in strategy, we targeted the four co-receptors representing the main chem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 168 publications
(293 reference statements)
2
65
1
Order By: Relevance
“…Tuning IRs form a functional complex with at least 1 or more co-receptors (Abuin et al, 2011; Ai et al, 2013), which might influence their functional properties (Task et al, 2022). To examine this, we utilized two probe whole mount fluorescent in situs to identify which IR co-receptors were co-expressed in the same cells as the 4 highly expressed tuning IRs.…”
Section: Resultsmentioning
confidence: 99%
“…Tuning IRs form a functional complex with at least 1 or more co-receptors (Abuin et al, 2011; Ai et al, 2013), which might influence their functional properties (Task et al, 2022). To examine this, we utilized two probe whole mount fluorescent in situs to identify which IR co-receptors were co-expressed in the same cells as the 4 highly expressed tuning IRs.…”
Section: Resultsmentioning
confidence: 99%
“…Taken together, our results suggest that Gr64b plays no significant role in modulating odor sensitivity or specificity in Or47aexpressing OSNs even though they are co-expressed in the very same neurons. (Task et al, 2022) and also in Aedes aegypti (Younger et al, 2022). Both of these studies demonstrated co-expression of the olfactory co-receptor (Orco) and multiple ionotropic co-receptors, Ir8a, Ir76b and Ir25a, in multiple OSN classes in the antenna and maxillary palps.…”
Section: Functional Implications Of Gr64b On Olfactory Coding In Ab5b...mentioning
confidence: 84%
“…However, surprisingly, it was in the recent study by Task et al (2022) observed that a few Orco and Ir25a positive neurons also innervate the V glomerulus sparsely, pointing to a wider possibility of overlap between these three gene families, but which could be revealed only after using more effective expression systems (Task et al, 2022). Similarly, the VM6 glomerulus, which was earlier considered a singular entity, was shown to be innervated by subpopulations of (Vulpe et al, 2021) and also by Ir25a positive OSNs (Task et al, 2022). Further, it was shown that the VA6 glomerulus (corresponding to Or82a) was innervated by OSNs expressing multiple coreceptors, including Orco, Ir25a, Ir8a and Ir76b, while, interestingly, the DM3 (corresponding to Or47a and Or33b) was innervated only by Orco positive neurons.…”
Section: Functional Implications Of Gr64b On Olfactory Coding In Ab5b...mentioning
confidence: 90%
See 2 more Smart Citations